STRATEGI PENGEMBANGAN SORGUM DI KABUPATEN WONOGIRI - Muhammad Syafruddin; Mohd. Harisudin; Emi Widiyanti (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2015)
This study aims to determine the potential of sorghum as compared to other food  commodities,  the  condition  of  internal  and  external  factors  of  sorghum,  and alternative  strategies  that  can  be  applied  in  Wonigiri.  This  study  uses  descriptive analytical  basis.  The  research  location  in  Wuryantoro,  Eromoko,  Pracimantoro, Giritontro,  and  Batuwarno  on  Wonogiri.  The  informants  are  choosen  intentionally (purposive). The data analysis that has been used is Exponential Comparative Method (ECM) and SWOT Matrix. ECM analytical result shows that sorghums currently ranks six compared with eight other food commodities with a value of ECM 14.535.912,505.SWOT matrix produced eight alternative strategies that can  be applied in Wonogiri. The  expansion  of  planting  area  and  guidance  from  goverment,  guidance  on  grain sorghum  processing  into  refined  products,  conduct  the  bussiness  meeting  with investors for large-scale processing of sorghum, counseling and regular coaching on how to make good cultivation of sorghum, provision of training and support of postharvest technology, cooperation with the food processing industry, the government’s role  in  determining  the  selling  price  and  the  promotion  of  sorghum,  increased  interaction between researchers, extension, marketers, policymakers and farmers.